Analisis Kelayakan Aspek Finansial Industri Kerajinan Kerang Mutiara (STUDI Kasus Pada UD. Mutiara Indah) - Wilma Latuny (ARIKA, 2010)
Shell Pearl industry become group of industries which is production using sea resources that can be focus of development. In fact, these industries exist and develop in Ambon but they have not given regional economic contribution optimally. For observing how far these industries can survive, develop and give profit for community and government, the further analysis of feasibility study must be needed. Therefore, one of important aspect of analysis is financial aspect taking case in UD Mutiara Indah. The result of research obtain that in financial aspect of analysis is feasible by calculating NPV = Rp.406.423.640 > 0; Payback Period below 5 years which is 3 years 2 months 6 days; Profit could achieved of 156 unit of selling and losses could reached of less 31,3 %.